(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In Indian Banking sector must build up a personnel management framework on an efficient premise and take up personnel management policies and practices that energetic the requirements of the banking sector. The Indian Banking industry must be overseen by banking experts so as to be forceful and to grab hold of the products of the sector on the worldwide dimension. This paper thinks about an audit of personnel management policies and practices in the banking sector in India chiefly in Public Sector Banks with thought of some significant markers of banking sector, for example, work investigation, recruitment and choice, preparing and improvement, execution evaluation and pay. Subsequently, the proposals will bolster appropriate ramifications of personnel management rehearses in the Indian public sector banks.